2013
DOI: 10.1111/eip.12010
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of school mental health literacy programs to address knowledge, attitudes and help seeking among youth

Abstract: Research into school-based mental health literacy is still in its infancy and there is insufficient evidence to claim for positive impact of school mental health literacy programs on knowledge improvement, attitudinal change or help-seeking behaviour. Future research should focus on methods to appropriately determine the evidence of effectiveness on school-based mental health literacy programs, considering the values of both RCTs and other research designs in this approach. Educators should consider the streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(195 citation statements)
references
References 37 publications
6
170
0
7
Order By: Relevance
“…10 However, such results may reflect changes in treatment-seeking behaviour. 27 There have been substantial efforts made to reduce the stigma surrounding mental illness, 28,29 and awareness of mental illness has increased among medical professionals and the general public. [28][29][30] As mental health literacy increases, parents and caregivers are presumably more likely to recognize mental health problems and refer children to professional care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 However, such results may reflect changes in treatment-seeking behaviour. 27 There have been substantial efforts made to reduce the stigma surrounding mental illness, 28,29 and awareness of mental illness has increased among medical professionals and the general public. [28][29][30] As mental health literacy increases, parents and caregivers are presumably more likely to recognize mental health problems and refer children to professional care.…”
Section: Discussionmentioning
confidence: 99%
“…27 There have been substantial efforts made to reduce the stigma surrounding mental illness, 28,29 and awareness of mental illness has increased among medical professionals and the general public. [28][29][30] As mental health literacy increases, parents and caregivers are presumably more likely to recognize mental health problems and refer children to professional care. 31,32 This may explain why studies using reports from parents and teachers have reported increases in rates of child and adolescent mental illness, 3,4 and why diagnosed rates of mental health problems have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full search strategy is provided in the Appendix A. Additional data sources included reference lists of appropriate existing systematic literature reviews [29,30,[32][33][34][35][36]. The relevant references from these reviews were included in the data set.…”
Section: Search Strategymentioning
confidence: 99%
“…• Mental health education programmes in schools can improve mental health knowledge of children (61). While most studies of school programmes have been carried out in high-income countries, one of the best evaluated in a low-income country was carried out in rural Pakistan.…”
Section: Promote Mental Health Literacy and Reduction Of Stigma Throumentioning
confidence: 99%